Congenital and infantile malignant melanoma of the scalp: A systematic review. (September 2017) - Tariq, Sohaib; Shallwani, Hussain; Waqas, Muhammad; Bari, Muhammad Ehsan
Abstract: Congenital and infantile malignant melanomas are rare and typically carry poor prognosis. The purpose of this article was to review the data on congenital and infantile malignant melanomas of the scalp in order to understand its presentation, diagnosis, management, and outcomes of congenital melanoma of scalp. We searched PubMed, CINAHL and Cochrane databases. Ten cases of congenital and 3 cases of infantile malignant melanoma of scalp were identified. The diagnosis was confirmed by biopsy and histological analysis for confirmation. The prognosis depends on the origin of disease (congenital melanocytic nevus, transplacental metastasis, or de-novo), tumor thickness, the presence of ulceration and/or necrosis, and anatomic site (scalp lesions having poor prognosis). The most commonly used treatment of the reported cases of congenital and infantile melanoma was surgical excision of the primary lesion. Further modes of treatment may be extrapolated from the treatment of childhood and adult melanomas. Highlights: Congenital and infantile malignant melanomas are rare. Surgery is the mainstay of treatment. Prognosis of the condition remains poor.